Penser l'évaluation des recherches participatives en termes d'enquêtes : quels rapports avec les visées heuristique et praxéologique ? - Lucie Mottier Lopez (Université de Provence, 2020)
This theoretical paper questions the critical function of evaluation for heuristic and praxeological aims of participatory research. In continuation of previous publications, it presents a model for the evaluation of participatory research from the point of view more specifically of the referentialization and normalization processes involved. The article underlines the prescriptive or descriptive nature of normalization at work in a dialectical relationship between referents and referees, and always in relation to acting situated contexts. It takes the example of the double likelihood criterion associated with collaborative research to test theoretical modelling. The evaluation takes the form of surveys; it is expressed in the form of questions that echo indeterminate situations around the double social relevance of the research, the double methodological rigour and the double fecundity of the results. The article shows that some surveys are specific to the heuristic or praxeological aim of participatory and collaborative research; others also ask to investigate the articulation between the two aims that can be mutually enriching.